Índices BAUX revisado, APACHE II y ABSI como predictores de mortalidad en grandes quemados - Bazán Moya, Erick Paúl (2022)
Severe burn damage the respiratory mucosa and destroy epithelial tissue, resulting in systemic, metabolic, and sometimes fatal consequences. For decision-making, it is necessary to have easy-to-access predictors of mortality. The study's objective was to evaluate and contrast the performance of the rBaux, ABSI, and APACHE II indices as indicators of mortality in patients with significant burns. 20 papers were chosen for a bibliographic analysis, which included information on mortality, accuracy, sensitivity, and specificity of the rBaux, ABSI, and APACHE II indexes. According to AUC, the accuracy of the rBaux, ABSI, and APACHE II indices was 0.84 to 0.99, 0.85 to 0.94, and 0.64 to 0.93 correspondingly. In terms of sensitivity, APACHE II scored the highest while ABSI scored the lowest, while in terms of specificity, ABSI scored the highest while APACHE II scored the lowest. The measurement of the inhalation injury and the burnt body surface area is the primary factor in the efficiency of the indices in burns; APACHE II exhibits less precision since it does not incorporate these factors. In severe burn patients, the rBaux index performed better as a predictor of mortality than ABSI and APACHE II.